The Interaction Effect of Perceived Social Support and Perceived Stress on Acculturative Stress among Ethiopian International Students in India - Malhotra, Nalini; Seifu, Kefale (International Journal of Psychosocial Rehabilitation, 2020)
The current study has investigated the interacting effect of perceived social support, components of perceived social support (support from family, friend, and significant others) and perceived stress on acculturative stress among Ethiopian international students (N=280) in India. Purposive sampling technique was used to select respondents from five identified universities of the country. Acculturative stress scale, perceived stress scale, and multidimensional perceived social support scale were used for data collection. Descriptive statistics, Pearson moment correlation, and process macro of Hayes were applied in order to analyze the hypotheses coined. The results of the current study’s howed: perceived social support, components of perceived social support (support from family, friend, and significant others) were significantly and negatively associated with acculturative stress, however, with varying degrees. Perceived stress was significantly and positively related to acculturative stress, i.e. when perceived stress increases acculturative stress also will increase. Perceived social support (in its total score) moderated the effect of perceived stress on acculturative stress, i.e. those international students who report a high level of perceived social support have a lower association between perceived stress and acculturative stress in comparison to students who report low levels of perceived social support. Moreover, components of perceived social support (support from friend and significant others) buffered the effect of perceived stress on acculturative stress, i.e. those international students who report a high level of support from friend and significant others have a lower association between perceived stress and acculturative stress in comparison to students who report low levels of support from friend and significant others. However, in the current study support from family could not moderate the relationship between perceived stress and acculturative stress. Limitations were discussed and recommendations were forwarded for institutions which give admission to foreign students and ministries which send these students abroad for study.